The development of a Filipino adolescent anxiety scale - De Guzman, Ligaya Sison
The study deals with the development of a Filipino Adolescent Anxiety Scale (FAAS) that is reliable, relevant and valid. It investigates the relationship between anxiety scores and selected variables. The study aims to help counselors and educators in getting to know their charges better thus enabling them to make appropriate measures to help the adolescents overcome their handicaps.